Blood Viscosity and Haemostasis in the Nephrotic Syndrome - McGinley, E; Lowe, G D O; Boulton-Jones, M; Forbes, C D; Prentice, C R M (Thrombosis and Haemostasis, 1983)
Blood viscosity and its major determinants (haematocrit, plasma viscosity and fibrinogen) as well as several haemostatic variables were measured in 21 patients with the nephrotic syndrome, and 21 controls matched for age, sex, smoking habit and serum creatinine. Blood viscosity was significantly increased in the nephrotic group, measured at a low shear rate (mean increase 41%, p<0.01) and at a high shear rate (mean increase 25%, p <0.01). Haematocrit was not significantly increased, but plasma viscosity was significantly higher (p <0.01), associated with increased plasma macroglobulins especially fibrinogen, which was increased to double the plasma concentration of the control group (p <0.01). Nephrotic subjects also had increased plasma levels of a2-macroglobulin, factor VIII activity, factor VIC antigen and beta-thromboglobulin; differences in antithrombin ID, fibrin degradation products, plasminogen, and platelet count were not significant.We suggest that increased blood and plasma viscosity may play a role in the vascular complications of the nephrotic syndrome.
Keywords: Nephrotic syndrome; Viscosity; Haemostasis